Miltefosine and polyhexamethylene biguanide: a new drug combination for the treatment of Acanthamoeba keratitis - ARICI, MUSTAFA KEMAL; POLAT, ZEHRA; WALOCHNIK, Julia; OBWALLER, Andreas; Vural, Ayse; DURSUN, AYHAN; ARICI, MUSTAFA KEMAL (My University, 2014)
BackgroundIn this study, a series of compounds - miltefosine, polyhexamethylene biguanide, chlorhexidine and propamidine isethionate - and combinations of the latter three agents with miltefosine were prepared and used in a rat model for the topical treatment of Acanthamoeba keratitis.